Characteristics of People With and Without Laboratory-Confirmed SARS-CoV-2 Infection During Pregnancy, Massachusetts, March 2020–March 2021. (July 2022) - Shephard, Hanna M.; Manning, Susan E.; Nestoridi, Eirini; Brown, Catherine; Yazdy, Mahsa M.
Objectives: Pregnant people infected with SARS-CoV-2, the virus that causes COVID-19, are at increased risk for severe illness and death compared with nonpregnant people. However, population-based information comparing characteristics of people with and without laboratory-confirmed SARS-CoV-2 infection during pregnancy is limited. We compared the characteristics of people with and without SARS-CoV-2 infection during pregnancy in Massachusetts. Methods: We compared maternal demographic characteristics, pre-pregnancy conditions, and pregnancy complications of people with and without SARS-CoV-2 infection during pregnancy with completed pregnancies resulting in a live birth in Massachusetts during March 1, 2020–March 31, 2021. We tested for significant differences in the distribution of characteristics of pregnant people by SARS-CoV-2 infection status overall and stratified by race and ethnicity. We used modified Poisson regression analyses to examine the association between race and ethnicity and SARS-CoV-2 infection during pregnancy. Results: Of 69 960 completed pregnancies identified during the study period, 3119 (4.5%) had laboratory-confirmed SARS-CoV-2 infection during pregnancy. Risk for SARS-CoV-2 infection was higher among Hispanic (adjusted risk ratio [aRR] = 2.3; 95% CI, 2.1-2.6) and non-Hispanic Black (aRR = 1.9; 95% CI, 1.7-2.1) pregnant people compared with non-Hispanic White pregnant people. Conclusions: This study demonstrates the disproportionate impact of SARS-CoV-2 infection on Hispanic and non-Hispanic Black pregnant people in Massachusetts, which may widen existent inequities in maternal morbidity and mortality. Future research is needed to elucidate the structural factors leading to these inequities.